The content of microelements in fruits of the oriental persimmon (Diospyros kaki) and its dietary role in remedying micronutrient deficiency in the region - N. Bakhshaliyeva; K. Aliyeva; J. Mammadov; A. Hummatov (Regulatory Mechanisms in Biosystems, 2023)
The relevance of the problem under study lies in the need to develop innovative approaches to the introduction of fruit crops into the diet to avoid the loss of nutrients and thus help prevent micronutrient deficiency in the human body. In this regard, the purpose of this article is to study the content of biologically active substances in the products of promising persimmon varieties and their effect on the normal functioning of the thyroid gland. The following results were obtained during the study: soil and climatic conditions affecting the nutritional value of the agricultural product were presented. It was established that Shaki-Zagatala economic region is an iodine deficiency endemic area and belongs to the zone of moderate iodine (I) deficiency. The quantity of macro- and microelements in fruits of 20 varieties of Oriental persimmon (Diospyros kaki) bred by folk selection growing in Shaki-Zagatala economic region was studied and compared by regions; the use of persimmon plants in the food industry as a way of increasing the amount of iodine in the human body was substantiated. It has been proved that in order to eliminate iodine deficiency, it is advantageous to eat more food enriched with iodine from fruits of the Oriental persimmon (D. kaki), which is rich in microelements. The role of awareness – raising activities among the population regarding health disorders associated with iodine deficiency was revealed. The practical value of the article materials consists in obtaining detailed information about biochemical composition of Oriental persimmon fruit (D. kaki) for the purpose of iodine deficiency prevention. The technologies of processing and storage of the product in fresh and processed form to preserve the useful properties of persimmon have been proposed in order to increase the profitability of production and increase the level of sales of products in the Shaki-Zagatala economic region of Azerbaijan.